Digital Technology Approach In Chemistry Education: A Systematic Literature Review - Sariah Binti Ali; Corrienna Abdul Talib; Abubakr Muhammed Jamal (Journal of Natural Science and Integration, 2023)
This study systematically reviews empirical studies on digital learning technologies and related instructional techniques for chemistry education from 2020 to 2022. Using the PRISMA criteria, the relevant article's history was followed using the Web of Science, Scopus, and ERIC databases. In this digital era, studies on pedagogical innovations mixed with new technologies are proliferating as a result of technological progress and the emergence of Artificial Intelligence (AI) technology. A growing corpus of empirical research indicates the potential for incorporating digital technology in diverse educational settings. Various new technologies, including robotics, learning analytics, virtual reality (VR), and augmented reality (AR), have found extensive use and have bright futures in the field of chemistry education. According to the current study, VR and digital learning apps were the most completely examined among the recognized technologies employed in chemistry education. The main areas of interest in the classroom were visualization, engagement with chemical structures, and hands-on activities. The findings of this study, which examined impact, advantages, disadvantages, and challenges of online technology in the process of chemistry education, lends insight on the rapidly evolving disciplines of chemistry education research and technologically enhanced instruction.Keywords: digital, chemistry, education, technology, virtual.